Pempheris ufuagari sp. nov., a new species in the genus Pempheris (Perciformes, Pempheridae) from the oceanic islands of Japan - Koeda, Keita; Yoshino, Tetsuo; Tachihara, Katsunori (Zootaxa, 2013)
Pempheris ufuagari sp. nov. is described based on 10 specimens, 143.9–196.8 mm in standard length, collected from Mi-nami Daito Island and Ogasawara Islands, which are oceanic islands of Japan. Pempheris ufuagari is characterized by a distinct black spot on the pectoral fin base, a bright yellow dorsal and caudal fin, and a blackish band on the outer margin of the anal fin. Pempheris oualensis also has a large body and a distinct black spot on the pectoral fin base, and forms mixed schools with P. ufuagari, but can be distinguished by the different fin coloration (dorsal and caudal fin brown or pale; no blackish band on anal fin margin), and the presence of a villiform tooth band extending outside the lips. Although P. otaitensis, which is found in French Polynesia and Samoa, has similar coloration as P. ufuagari, the latter has lower scale counts than those of the former species: pored lateral-line scales 62–71 (vs. 70–79); scale rows above lateral line 6 1/2–7 1/2 (vs. 8 1/2); predorsal scales 37–43 (vs. 44–48).